2005
DOI: 10.1162/0898929053467622
|View full text |Cite
|
Sign up to set email alerts
|

Common Mechanisms for Working Memory and Attention: The Case of Perseveration with Visible Solutions

Abstract: Everyone perseverates at one time or another, repeating previous behaviors when they are no longer appropriate. Such perseveration often occurs in situations with working memory demands, and the ability to overcome perseveration has been linked to brain regions critical for working memory. Many theories thus explain perseveration in terms of working memory deficits. However, perseveration also occurs in situations without apparent working memory demands, in which the visible environment specifies appropriate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 36 publications
2
51
0
2
Order By: Relevance
“…45 Researchers have begun to demonstrate associations between attentional control characteristics and cognitive regulatory tasks involving working memory and inhibitory control in preschool children, 28,36,[47][48][49] as well as in the neural network modeling of cognitive tasks in infants. 50 It is clear that from early in life, attentional control and working memory not only are coupled with each other, but also underlie many other aspects of cognitive performance associated with school readiness. 27,47 As with other regulatory abilities, working memory and cognitive regulation demonstrate great changes during infancy and early childhood.…”
Section: Development Of Cognitive Regulatory Behaviorsmentioning
confidence: 99%
“…45 Researchers have begun to demonstrate associations between attentional control characteristics and cognitive regulatory tasks involving working memory and inhibitory control in preschool children, 28,36,[47][48][49] as well as in the neural network modeling of cognitive tasks in infants. 50 It is clear that from early in life, attentional control and working memory not only are coupled with each other, but also underlie many other aspects of cognitive performance associated with school readiness. 27,47 As with other regulatory abilities, working memory and cognitive regulation demonstrate great changes during infancy and early childhood.…”
Section: Development Of Cognitive Regulatory Behaviorsmentioning
confidence: 99%
“…Theories of the developmental origins of cognitive control converge in positing that children engage these same proactive processes, but in a weaker form, with less strength or stability (9,10), less resistance toward habitual responses (1, 2), or degraded complexity (8,11). For example, according to one influential theory (8), developmental change in cognitive control is driven by ''age-related improvements in the complexity and scope of children's intentional, top-down processes.''…”
mentioning
confidence: 99%
“…10). Finally, neural network models have simulated developmental improvements in cognitive control via parametric increases in the strength of recurrent connections for maintaining task-relevant representations (9).…”
mentioning
confidence: 99%
“…From a broad perspective, an informal analysis by showed that approximately 75% of the published developmental computational models have been connectionist. These models have accounted for some key developmental phenomena, such as tradeoffs in brain development (McClelland, McNaughton, & O'Reilly, 1995;O'Reilly & Munakata, 2000), nonlinear patterns of development (Plunkett & Marchman, 1993;Rogers & McClelland, 2004;, perseveration (Munakata, 1998;Stedron, Sahni, & Munakata, 2005), and the emergence of semantic knowledge (Rogers & McClelland, 2004). Second, this article focuses on connectionist models in the interest of depth over breadth.…”
Section: Why Focus On Pdp Models?mentioning
confidence: 99%
“…Development is modeled by increasing the network's ability to sustain activity over time. For example, in a model of the A-not-B error, Munakata (1998) and Stedron et al (2005) manipulated the persistence of hidden unit activity by changing the strength of the recurrent weights on these units. These recurrent weights were designed to reactivate the hidden units whose activity decayed over time.…”
Section: Commonly Modeled Phenomenamentioning
confidence: 99%